¿Ejercicio o restricción? De la libertad de expresión por parte de la Supercom hacia los artículos y editoriales del diario El Comercio - Cox Avilés, Braulio Antonio (2016)
The sanctions and processes that the newspaper “El Comercio” has received against them between 2014 and 2015, through the application of the Organic Law of Communication (LOC), expose for us the existence of an arbitrary imposition of contents executed by the government, which has led to a self-censure of the media in order to prevent a future sanction. At the same time, the dispute for guaranteeing the accomplishment of the right of communicating and the space of power, between the Superintendence of Information and Communication (SUPERCOM) and private media, have led as a result that the citizenship is left out of the public matters of the country. For this work, there have been selected six cases, where you may estimate that the Law has been used to sanction, through denunciations executed by the citizens or through letters emitted by the SUPERCOM. From these six processes, the most representative was the unjustified sanction that received the media on April 15, 2015, because of the publication of the journalistic article “The project Coca-Codo will have an adjustment of USD 606 millions, where there may be identified some elements that denote that LOC is being used to impose intentionally a ruling truth. With all this, it may be said that the application of the Organic Law of Communication and the execution of journalism in Ecuador, in this moment is immerse in a legal and politic argument, which has left out all the citizenship interests.